If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+16=6x-6
We move all terms to the left:
3x+16-(6x-6)=0
We get rid of parentheses
3x-6x+6+16=0
We add all the numbers together, and all the variables
-3x+22=0
We move all terms containing x to the left, all other terms to the right
-3x=-22
x=-22/-3
x=7+1/3
| .7h+14=8.4h | | 11/4*a=-1/2 | | 3x-2=4x+-x | | 7x-12-x²=0 | | 3x+41/2=-3+6x | | 8−9m=–10m | | 12/n=9/6 | | a4=28 | | -7-7x=6^3 | | (9x+1)=88 | | w÷7=14 | | 14x=723 | | 6^4x=15 | | 6(3x+2x+4)=-6x+96 | | p+14+2p2=18 | | (2x+11)+(3x-46)=180 | | 0.79166666666=-0.83333333333t-0.25 | | 8w-24=-5(2-3w | | 4x+22=7x+16 | | 5x-10=5x+ | | -3(2x-4)=4(3/2x3) | | -7-7x=6•3 | | 31+p=52 | | V-W=y | | j-1/7=1/7 | | 6x^2-2=-74 | | 8-(-5x)=103 | | 5x-9+2=10x+24 | | (3y-8)+(3y-22)=180 | | -7-7x=6x3 | | -2x=6=19 | | 5(u+5)=-3(3u-3)+8u |